The effect of profitability and leverage on tax avoidance with interest coverage as a moderating variable - Murdhaningsih Murdhaningsih; Nabilah Farras Luthfi; Bunga Anisah Harared (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
This study aims to examine the effect of financial performance indicators—Return on Assets (ROA), Return on Equity (ROE), Debt to Asset Ratio (DAR), and Debt to Equity Ratio (DER)—on tax avoidance, with the Interest Coverage Ratio as a moderating variable. The research sample comprises industrial sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. Using panel data regression analysis, the results of Model 1 show that DAR has a significant effect on tax avoidance. Furthermore, model 2 shows that the Interest Coverage Ratio moderates the relationship between ROA, ROE, and DAR on tax avoidance, but is not significant on DER. These findings indicate that the financial structure and the company's ability to cover interest expenses influence tax avoidance behavior. This study contributes to understanding how internal financial factors influence corporate tax planning strategies. Further research is recommended to explore broader sectors and add other financial and non-financial variables to obtain a more comprehensive picture of tax avoidance behavior.. Public Interest Statement This study helps the public understand how companies' financial conditions, particularly debt levels and interest payments, influence their tax planning behavior. The findings are helpful for regulators, investors, and taxpayers to identify potential tax avoidance practices and promote fair taxation.